2001
DOI: 10.1093/jn/131.9.2424s
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition among Older Adults in Africa: the Situation at the Beginning of the Millenium

Abstract: Most Africans enter old age after a lifetime of poverty and deprivation, poor access to health care and a diet that is usually inadequate in quantity and quality. However, nutrition interventions in African countries are directed primarily toward infants and young children, as well as pregnant and lactating women. This situational analysis focuses on two key areas to identify priorities for future research and policy development: the nutritional status of older Africans and determinants of undernutrition. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 11 publications
2
77
1
2
Order By: Relevance
“…26 South African elderly tend to be community residents, living in multiple generational family households, due to limited institutionalized care. 27 However, unlike Nigerian elderly, South African elderly do receive financial support through the nationalized pension system. 27 Thus, one observed pathway to stimulate initiatives focusing on active aging and optimal psychosocial health status for elderly can include the use of home-based, self-care guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 South African elderly tend to be community residents, living in multiple generational family households, due to limited institutionalized care. 27 However, unlike Nigerian elderly, South African elderly do receive financial support through the nationalized pension system. 27 Thus, one observed pathway to stimulate initiatives focusing on active aging and optimal psychosocial health status for elderly can include the use of home-based, self-care guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…27 However, unlike Nigerian elderly, South African elderly do receive financial support through the nationalized pension system. 27 Thus, one observed pathway to stimulate initiatives focusing on active aging and optimal psychosocial health status for elderly can include the use of home-based, self-care guidelines. 26 As such, in both Nigeria and South Africa, challenges related to population aging, such as psychosocial health status, remain a significant priority for future research and policy development.…”
Section: Introductionmentioning
confidence: 99%
“…This group is at high risk of having a poor micronutrient status due to inadequate household food security (Charlton & Rose, 2001), deficient dietary intakes (Johnson & van der Westhuizen, 1992;Bester et al, 1993;) and lack of financial provision for old age (Ferreira et al, 1992). Sugar is a cheap commodity, which is consumed in relatively large amounts in black children in the country (Labadarios et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…other factors contributing significantly to the nutritional status included income control, gender, tooth mobility, caries experience and the following risk factors: poor manual dexterity, physical disability, alcoholism, tobacco use, low budget for food, recent injury, and poor eyesight (table 7). studies have shown that old age for most africans is normally associated with poor access to health care and a diet that is usually inadequate in quantity and quality (20). nutrition interventions in africa have however focussed on children and pregnant/lactating women leaving out old people who are not considered as a priority group.…”
mentioning
confidence: 99%